Estudo da susceptibilidade e resposta dos biofilmes de estafilococos aos agentes antimicrobianos - Leite, Bruna de Arruda (Universidade Federal de São Carlos, 2013)
The staphylococci belong a diverse group of bacteria that cause diseases ranging from minor skin infections to death-threatening bacteraemia. The two major opportunistic pathogens of this genus, Staphylococcus epidermidis and S. aureus are the most frequent causes of nosocomial infections and infections associated with the use of medical devices. Staphylococci, is the leading cause of infections associated with biofilm formation. Biofilmrelated infections are challenging to treat with conventional antimicrobial agents, limiting the efficacy of antibiotic therapy and becoming a crucial problem for treatment of chronic infections. Therefore, the main aim of this thesis was to study the susceptibility of staphylococcal biofilm cells against antimicrobial agents. For that, it was evaluated in vitro activities of N-acetylcysteine (NAC), rifampicin, linezolid, daptomycin and vancomycin alone and in combination on biofilm cells of Staphylococcus epidermidis and S. aureus. The activities of antimicrobial agents were evaluated in concentrations CIM, 10xCIM and peak serum. The biofilms susceptibility to agents studied was assessed through, colony-forming units (CFU/ml), staining with crystal violet (CV) that is the measure total biofilm biomass and cellular activity using XTT reduction assay. The results of viable cells (expressed as log10 CFU/ml) to N-acetylcysteine alone, in the concentration 10xCIM on both the biofilms of staphylococcal evaluated showed a greater effect compared with other antimicrobial agents evaluated, with reductions of approximately 4-5 log10. The combination NAC (10xCIM) - vancomycin (independent of concentration evaluated) showed a greater reduction (p<0.05) on viable cells of S. epidermidis and S. aureus, compared with other combinations evaluated. This combination presented a reduction about of 5-6 log10 CFU/ml. The results of CV showed loss the total biofilm biomass and were observed decrease in the metabolic activity measured by the XTT, these results are in very good agreement with those obtained in terms of cell viability. In conclusion, the results obtained in the studies of this thesis constitutes a promising therapeutic strategy in the treatment of infections associated with biofilm formation by S. epidermidis and S. aureus. In addition, the use of antimicrobial agents in combinations may be an alternative for monotherapy, thus avoiding the development of resistance.
Study of susceptibility and response of staphylococcal biofilms to antimicrobial agents
Keywords: Biofilme; Staphylococcus epidermidis; Staphylococcus aureus; Agentes antiinfecciosos; Biofilm; Antimicrobial agents; OUTROS